Analysis of wind effect on the canopy structure - Fatin Sufina, Abdul Rashid (2013)
Frequently in Malaysia number of damage due to wind storm are occurred. Canopy is widely used by Malaysian. However, the number of canopy damage was some of the most severely occur in Malaysia. No version of the predominant standard and commentary for wind load design in Malaysia introduced for the the first time for the open canopy. in this study the typical type of canopy are identified. Both cases are examined with wind load in order to identify the possibility of wind speed that can cause damage to canopy. From the result it is show that if wind speed 11m/s the failure of the canopy will occur. It can be conclude that canopy structure will be failure easily. For the record at Malaysia Meteorology Department, it show that during thunderstorm wind speed are recorded about 18m/s. Future study need to be calculated in order to implement the understanding of canopy due to wind load.